Patient‐reported barriers to medication adherence in heart failure in Scotland. (24th January 2019) - Forsyth, Paul; Richardson, Janice; Lowrie, Richard
Abstract: Objectives: Medication adherence is the end result of a complex set of interwoven factors. Non‐adherence with medication in heart failure patients is associated with excess mortality and morbidity. Studies describing interventions to improve adherence in heart failure are limited by a lack of robust methods and inconsistent outcomes. The aim of this evaluation was to explore the barriers to medication adherence in Scottish heart failure patients in order to inform the development of complex interventions. Methods: Qualitative patient interviews. Participants were aged ≥18 years with current or previous signs or symptoms of clinical heart failure, reduced left ventricular ejection fraction ≤45% and confirmed adherence of <80% in tablet counts of heart failure therapy. Thematic analysis was employed. Key findings: Eleven patients were recruited. The median age was 79 years old, and participants were typically from socially deprived communities. Participants were prescribed a mean 9.9 different medications per day. Seven distinct themes emerged around barriers to medication adherence: co‐morbidity; treatment burden; health literacy; trust in NHS; socioeconomic factors; autonomy and health expectations. Conclusions: The factors affecting medication adherence in heart failure are multi‐factorial and are unlikely to be improved by one single‐faceted intervention. Future interventions need to treat patients holistically, build their trust as partners, simplify complex treatment regimens where possible and involve educational and social elements. The skill set and opportunities afforded to pharmacists may be well placed to deliver many of these aspects but this would need tested in the context of the development of complex interventions.